'Sistas' and Aunties: sport, physical activity, and Indigenous Australian women. Issue 1 (2nd January 2016) - Stronach, Megan; Maxwell, Hazel; Taylor, Tracy
Abstract : Indigenous women have alarmingly low rates of participation in organized sport and physical activity (PA) in contemporary Australian society. To gain a better contextual and cultural understanding of the issues involved, we discussed the life experiences and the place of sport and PA with 22 Indigenous women. The research was guided by a culturally appropriate interpretative qualitative methodology. A complex amalgamation of cultural beliefs and traditions, history, gendered factors, and geography are presented in the women's stories. Sport and PA were highly regarded, providing the women with opportunities to maintain strong communities, preserve culture, and develop distinct identities as 'enablers'. The women called for culturally safe spaces in which to engage in PA and noted the need for Indigenous females to act as role models. The study provides preliminary understandings that can be used to facilitate greater sport and PA inclusion, and implications for future research are presented.